Электрофизические характеристики грунта в местах расположения энергообъектов Украины - Колиушко, Д.Г.; Руденко, С.С.; Колиушко, Г.М. (Електротехніка і електромеханіка, 2015)
На основании анализа результатов зондирования получено статистическое распределение слоистости грунтов в
местах расположения энергообъектов Украины, разработаны рекомендации о применимости метода эквивалентирования многослойных геоэлектрических структур при определении нормируемых параметров заземляющих устройств.
Доказана необходимость создания математической модели заземляющего устройства, расположенного в трехслойном грунте, а также новой установки для зондирования грунта, позволяющей увеличить глубину зондирования, и
средств интерпретации. На основі аналізу результатів зондування отримано статистичний розподіл кількості шарів ґрунту в місцях
розташування енергооб’єктів України, розроблено рекомендації щодо застосування метода еквівалентування
багатошарових геоелектричних структур при визначені нормованих параметрів заземлювальних пристроїв. Доведена
необхідність створення математичної моделі заземлювального пристрою, розташованого в трьохшаровому ґрунті, а
також нової установки для зондування ґрунту, котра дозволить збільшити глибину зондування, та засобів
інтерпретації. Purpose. Definition of the direction for further research to improve accuracy of the calculation of rated parameters of ground
grids based on the analysis of statistical databases of electrophysical characteristics of the soil. Methodology. To solve this
problem we compiled the statistical base of soil of Ukraine in
the location of electrical substation, we performed the statistical
analysis for the number of layers of geoelectric structure, and
electrical characteristics. In the experiments implemented the
comparing of accuracy calculation of the most typical three-layer
soil in the Ukraine, by the new three-layer model of ground grids
and the equivalent two-layer model, which used previously.
Results. On the results of analysis the ranges of the electrical
resistivity and statistical distribution for electro-physical characteristics of the soil are determined. The resulting distributions
allow to develop criteria for instruments, installations and means
of interpretation during the sounding of soil, as well as the requirements for mathematical models of ground grids. It was found
that the most typical for places of locations the electrical substations in Ukraine are three-layer geoelectric structures. In the
paper the statistical distribution for three-layer soil by type (Q, K,
H, A) are described. The results of numerical experiments show
that the use of methods to simplify of the multilayers soil does not
allow the calculation of grounding grids with high accuracy. In
the work recommendations for applicability the method equivalenting depending on the type of geoelectric structure are developed. Originality. For the first time, we obtained the statistical
distribution of stratification of the soil in the location of power
plant in Ukraine, determined the accuracy of the method to simplify a multi-layer soil in determining the rated parameters of
grounding grids. In the paper the necessity to develop a mathematical model of the grounding device located in the three-layer
soil is shown, as well as a new installation of soil sounding, which
allows to increase the depth of sounding and new means of interpreting the results of sounding Wenner installing a four-layers
geoelectric structure. Practical value The resulting recommendations for the applicability of equivalenting of multilayer soil, as
well as research in specific work areas would help to reduce costs
on materials and labours during the modernization and upgrade
of grounding devices, moreover it will increase the electrical
safety and reliable operation of electrical substation.